Catastrophes To Come: What Can Literature Tell Us?. (May 2016) - Lavocat, Françoise
Abstract: Can literature and the arts in general help to prevent catastrophes? In the article this question is entertained through examination of the contrast between ancient cultural productions (comprising those legends and sermons which constitute 'literature' in the larger sense) and contemporary fiction. The article shows, first of all, how ancient culture not only engaged in forward‐looking thought when it came to catastrophes through the attribution of responsibility and by recommending moral reform but also by constituting a memory of catastrophes and in making practical suggestions. Our contemporary world has been swamped with fictional treatments of catastrophes – treatments that might seem to have the power of heralding these catastrophes and certainly of nurturing an obsessive fear of them. But contemporary fiction (literary or filmic) principally expresses a consciousness of its own impotence; if literature can prepare people for catastrophes, it can only be along ethical lines. Abstract : It is possible that mythic and fictional catastrophes are able to place real catastrophes in perspective.